El método Singapur y las relaciones lógico matemáticas en los niños de 4 a 5 años en la Unidad Educativa del Milenio Bernardo Valdivieso de la Ciudad de Loja, periodo 2023- 2024 - Rogel Valdivieso, Dulce María (2024)
Logical-mathematical relationships are fundamental in the cognitive development of children, as they provide them with skills and tools to understand and solve problems in various areas of their environment. This research was carried out with the purpose of determining how the Singapore method strengthens the logical-mathematical relationships of 4 to 5-year-old children at the Bernardo Valdivieso Millennium Educational Unit in Loja city A mixed approach was used, enabling qualitative analysis of the activity guide applied to the children and the results obtained from the instrument used, as well as quantitative analysis allowing for the tabulation of data collected in the pre-test and post-test. It was conducted under a quasi-experimental design, as the independent variable was manipulated, resulting in positive outcomes in the dependent variable. The methods employed were inductive-deductive, which facilitated a concrete analysis of the study phenomenon leading to accurate conclusions, and analytical-synthetic, which aided in individually analyzing each variable and selecting the most relevant information to construct the theoretical framework. The instrument used was the Early Mathematical Evaluation Test (EMET), which assessed mathematical learning: classification, correspondence, counting, general number knowledge, and seriation. Through this, results were obtained regarding the level of development of children's logical-mathematical relationships, showing that initially, 9% were in the very high zone. An activity guide based on the Singapore method was applied, leading to significant improvement, reflecting a 76% increase in the very high zone and enhancing the mathematical skills of the children. This confirms the effectiveness of the Singapore method in improving this area, as notable improvements were observed in the students. Keywords: Cognitive Development, Skills, Singapore Method, EMET.